Choosing your First Dairy Project: A Parent' Guide - James Umphrey (EDIS)
This document is 4HDAP01 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published August 1996; Reviewed June 2002.